360° VR and Softball Umpire Decision-Making: Lessons and Insights - Kaiser, Keone (Auckland University of Technology, 2021)
Background: Despite the importance of effective sports officiating for athletes and fans across the world and across sports realms, research into improving the performance of these individuals has been lacking. Few, if any studies, have demonstrated effective methods for improving one of the key tasks of sports officials– accurate decision-making. Officials can improve their decision-making by accumulating experience officiating live games, but this takes time. As a complement to live-game experience and a way to train decision-making outside of a game, decision-making through broadcast video methods has been proposed and utilised. However, the ability of these methods to transfer skills to live games has been questioned. Due to their first-person perspective and accompanying features, 360° VR videos may offer improved decision-making accuracy training alternatives to 2D broadcast videos. Purpose: The current study examined and compared the use of 2D Broadcast videos and 360° VR videos by a cohort of softball umpires (N =17) to 1) assess sports official decision-making accuracy using 2D Broadcast videos and 360° VR videos; 2) compare Ecological Validity values between the 2D and 360° VR videos; 3) assess the connection between experience level and video condition; 4) obtain qualitative data on the video conditions through interviews of several softball umpires. Methods: A four-stage mixed-methods approach was used to gain more comprehensive and complementary results. Quantitative data was primarily gathered during the first three stages, while qualitative data was gathered during fourth stage. The results showed no significant differences in decision-making accuracy between the 2D Broadcast videos and the 360° VR videos (decision-making accuracy mean of 8.0 +/- 0.9 s.d. for 360° VR, 8.5 +/- 1.5 s.d. for 2D broadcast, p = 0.242), and no significant differences in accuracy by experience level on either video condition (novice accuracy mean of 8.5 +/- 1.4 s.d. on 2D broadcast and 8.0 +- 1.0 s.d. on 360° VR, expert accuracy mean of 8.5 +/- 1.7 s.d. on 2D broadcast and 8.0 +/-0.8 on 360° VR, p=0.961). The 360° VR videos received significantly higher EV values than the 2D Broadcast videos (7.1 +/- 2.0 s.d. on 360° VR, 4.4 +/- 1.9 s.d. on 2D broadcast video, p <0.001). Conclusion: Despite mixed results, the qualitative feedback from umpires supports the potential of 360° VR as a decision-making accuracy tool.
Keywords: Sports officials; Decision-making; Virtual Reality; Softball; 360 VR; Umpires